2008
DOI: 10.1037/1528-3542.8.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Affective learning increases sensitivity to graded emotional faces.

Abstract: How does the affective significance of emotional faces affect perceptual decisions? We manipulated affective significance by pairing 100% fearful faces with aversive electrical stimulation and hypothesized that increasing the significance of a stimulus via its prior history would lead to enhanced processing. After fear conditioning, participants viewed graded emotional faces that ranged from neutral to fearful. Faces were shown either in a color that was previously paired with shock or a color not paired with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 44 publications
9
43
0
3
Order By: Relevance
“…Finally, participants consistently rated the S3, S4, and S5 as fear expressive, while the S1 and S2 were consistently not rated as fear expressive ( Fig. 2D; see also Graham et al 2007;Lim and Pessoa 2008). Based on these results, a categorical boundary was determined to exist between the S2 and S3 (point of subjective equality), such that faces of 55% fear intensity and greater were reliably discriminated from faces of less fear intensity that appeared neutral.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, participants consistently rated the S3, S4, and S5 as fear expressive, while the S1 and S2 were consistently not rated as fear expressive ( Fig. 2D; see also Graham et al 2007;Lim and Pessoa 2008). Based on these results, a categorical boundary was determined to exist between the S2 and S3 (point of subjective equality), such that faces of 55% fear intensity and greater were reliably discriminated from faces of less fear intensity that appeared neutral.…”
Section: Methodsmentioning
confidence: 88%
“…The CS+ (S3) was intermittently paired with the US on 33% of generalization test trials (''steady-state'' generalization test) (Honig and Urcuioli 1981). These steady-state (''booster'' trials) reinforcement procedures are intended to extend the length of time over which responding can be measured and offset the effects of extinction and habituation (Mednick and Freedman 1960;Honig and Urcuioli 1981;Smith et al 2006;Lim and Pessoa 2008). One unpaired US was also delivered at the start of the second and third segment of the generalization test prior to any stimulus presentation to maintain general arousal.…”
Section: Generalization Testingmentioning
confidence: 99%
“…Our study provides a neural mechanism accounting for such a scenario that may happen in our daily lives, and suggests that the brain encodes threat stimuli in a way that modifies sensory processes to maintain better traces and allow more efficient detection, even in changing environments. While the prioritization of emotionallyrelevant information for attention and subsequent declarative memory has been extensively studied (Phelps and LeDoux, 2005;Vuilleumier et al, 2001), comparatively little is known about the impact of stimulus emotional significance on long-term perceptual representations and perceptual decisions (Chavez et al, 2013;Li et al, 2008;Lim and Pessoa, 2008;Resnik et al, 2011;Weinberger, 2004). Moreover, recent brain imaging studies suggest that the consolidation of aversive associations may benefit from post-encoding sleep (Menz et al, 2013;Pace-Schott et al, 2009;Sterpenich et al, 2007), but whether this also gives rise to enhanced perceptual sensitivity and discrimination ability for emotionally-relevant information has remained hitherto unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have provided strong evidence that the amygdalamediates the processing advantage of emotional items [2] . Lim and Pessoa [72] found that participants had increased sensitivity to shock-paired faces and patches relative to unpaired faces and patches during a neutral/fearful discrimination task, and they were more likely to report the faces and patches as fearful if they were shown in a color that was previously paired with shock.…”
Section: The Amygdalamentioning
confidence: 99%